Uma revisão crítica da legislação brasileira acerca de embalagens especiais de proteção à criança (Ergodesign & HCI, 2014)
RESUMO Este artigo é uma revisão bibliográfica em relação às Embalagens Especiais de Proteção à Criança (EEPCs), que apresenta os problemas de intoxicação, bem como o surgimento dessas embalagens. O artigo também aborda o Projeto de Lei nº 4841/94 em comparação com o atual protocolo de teste americano, visando apresentar sugestões de melhoria para os problemas encontrados. Design, Ergonmia, Embalagens   TITLE: A critical review of brazilian legislation about child-resistant packaging ABSTRACT 1 Context  Poisoning  is  one  of  the  problems  related  to  the  use  of  packaging.  According  to Bochner  [1],  in  2003,  the  main  cases  of  human  poisoning  reported  by  CEATOX/SP (Toxicology  Service  Center  of  São  Paulo)  were  medicines,  poisonous  animals  and household  cleaning  products.  So,  the  application  of  ergonomic  parameters  in  the  design of packaging should be a factor that minimizes some problems. The warnings on labels are the more conventional methods to prevent poisoning accidents  in  Brazil.  However,  they  are  not  sufficient  to  prevent  accidents  [2].  For  example, children that are less than 5 years old cannot read or understand the messages [3]. By the fact that  many accidents related to intoxication with children under five  years old were being reported, Child-Resistant Packagings (CRPs) became mandatory in the United States in 1970 [4]. In  the  first  25  years  after  the  establishment  of  the  Poisoning  Prevention  Packaging Act, the tests  with  new CRPs in the United States were  made only with children and adults  from  18  to  45  years  old.  Elderly  and  disabled  people  were  excluded  from  the tests  and  as  a  result  they  ended  up  having  a  lot  of  difficulty  to  access  the  CRPs. Therefore,  in  the  early  1990s,  the  Consumer  Product  Safety  Commission  (CPSC) recognized the  need to develop a  new  test protocol in order to  make the  CRPs  more effective to the consumers. Then in 1995, the  new  American test protocol arises [5]. This  protocol  describes  three  tests:  with  older  adults,  with  young  adults  and  with children, which are used to verify the design of new CRPs [6]. In the test with older adults, it is selected 100 subjects between 50 and 70 y.o. who do not have  any  physical  or  mental  disability.  These  individuals  have  up  to  5  minutes, and then another  minute at a  second test,  to open and close  the  packaging. The CRP passes the test if at least 90% of the subjects successfully perform the task. In  the  test  with  young  adults,  it  is  selected  100  adults  aged  between  18  and  45  y.o. who  do  not  have  any  physical  or  mental  disability.  It is  given  only  a  period  of  5 minutes to try to open and close the packaging. The test with children is done with a group of children between 42 and 51 months old. The number of children may vary from 50 to 200. The test for this group of individuals  can  last  up  to  10  minutes,  and  it  is  presented a demonstration  of  opening  when necessary. The CRP passes in the test if at least 80% of the subjects cannot open the packaging. In Brazil, CRPs are not mandatory, but there is the Bill 4841/94 [3] which determines the  use  of  such  packagings  with  medicines  and  chemical  products  for  domestic  use which present a risk to health, however, this project is in the Brazilian Congress since 1994.  This  project  is  based  on  other  legislation,  particularly  the  United  States  and Canada [7]. The Brazilian Bill has only two tests to  verify the  effectiveness of CRPs: a  test  with young adults and a test with children between 42 and 51 months old. These tests fol-low the same procedures of the American test protocol cited above. Thus, the aim of this study was to evaluate the Brazilian Bill compared to the legislation  of  the  USA, presenting  some  suggestions  for  problems  and  unconformities  encountered. 2 Method Literature review for analysis and comparison of the American test protocol with the Brazilian Bill 4841/94. 3 Results  Due to the lack of mandatory use of CRPs in Brazil, it generates a lack of standards in products, where the use of safety caps is up to the producing company.  It is common to find the opening instructions in English, and so, many Brazilian users do not under-stand the opening procedures. In  the  Brazilian  Bill  the  elderly  are  not  considered  in  the  packaging  tests.  It  can  be seen  that  Brazil  follows  the  old  test  protocol  of  the  United  States.  This  can  be  explained by the fact that the Brazilian Bill have emerged in 1994, while the reformulation  of  the  American  test  protocol  happened  only  in  1995.  However,  many  changes have been  made  in the  Bill, and the  introduction of a  test with elderly  people  should have been considered. Another unconformity found in the Bill 4841/94 is the assertion that is made concerning  the  CRPs,  where  it  is  said  that  such  packagings  are  simple  devices.  However, studies have shown that these devices become complex for many users [8-14]. Observing  the  inclusion  of  individuals  with  perceptive  disabilities  in  some  studies [13,14], it is found another problem with the Brazilian Bill. To participate in the CRP test, individuals need to be "normal", that is, without evident physical or mental disa-bility. However, a  fact that has been noted by Bix et al. [5] is that  a  wheelchair  user has an obvious physical disability, but at the same time  he/she has the movements of the upper limbs and this person could participate in tests. 4 Conclusions  For the Bill 4841/94 achieve a good quality in its content, it is important to take into account the principles of universal design and ergonomic requirements. It  is  suggested  that  the  Bill  obliges  the  CRP  opening  statements  to  be  written  in  the vernacular language, and preferably with illustrations. Furthermore,  products  containing  substantial  quantities  of  alcohol,  as  is  the  case  of mouthwashes  and  alcoholic  beverages,  should  be  distributed  in  CRP.  However  there would be a lot of complaint from consumers of alcohol, but the main objective is the safety of children. Tests with elderly above 70 y.o. should replace the tests with adults, because this age group is the one that often uses large amounts of drugs, which are required to be sold in CRPs, and it is also the age group that most shows difficulties when opening those packagings. However, the possibility of requesting drugs in normal packaging should also be mentioned in the Bill. Finally, it is suggested  to change the exclusion criteria of individuals in participating in the tests. As it has also been suggested by Bix et al.  [5], instead of excluding individuals  with  evident  physical  or  mental  disabilities,  the  ideal  would  be  that  all  the subjects  that  could pass  the screening test (described in the  American protocol)  with the  packagings that are  not  child-resistant should be considered able to participate  in tests. Thus, wheelchair users, for example, could participate in the test.  Design, Ergonomics, Packaging